Evidence for littoral convergence and sediment delivery to Mattole submarine canyon, Northern California - Joerger, Sarah T.; Smith, M. Elliot; Buscombe, Daniel; Mueller, Erich R. (Frontiers in Earth Science, 2024)
At geologic timescales, a significant proportion of the sediment eroded from continents is transferred from rivers to littoral cells, then through submarine canyons to deep ocean basins. Accumulation and occasional discharge of sediment from canyon headwall regions is a likely driver for the sediment gravity flows believed to be responsible for much of this mass transport, but the responsible mechanisms and event timescales in canyon heads are imprecisely defined, largely due to the drowning of canyon heads since the last glaciation and the resulting dearth of modern depositional environments to observe. We investigated a littoral cell adjacent to Mattole submarine canyon in Northern California to better understand the influence of bathymetry and coast shape on sediment trajectories and hypothesize that canyon heads promote littoral sediment accumulation due to bathymetric sheltering of the adjacent coast from waves and convergence of littoral cells exposed to varying wave direction. The uppermost gullies of Mattole Canyon extend to the littoral cell, and a train of sediment waves within the uppermost thalweg of Mattole Canyon suggests that gravity-driven flows of shore-derived sediment may have recently occurred. Mattole Canyon and nearby Mendocino Canyon flow into the deep Mendocino Channel, which has the highest observed Late Holocene sediment accumulation rates in Northern California. We documented the beach slope, grain size, and sediment provenance along 15 km of coast adjacent to Mattole Canyon and conducted numerical wave modeling to infer the dominant direction and magnitude of sediment transport, relative wave sheltering by bathymetry, and estimated sediment mobility in the vicinity of the canyon head over a multi-year period. South of the canyon headwall, in the vicinity of the Mattole River outlet, coarser sediment rich in metasandstone clasts and steeper beach slopes coincide with decadal-scale beach accretion. North of the canyon head, sediments are generally finer, beaches are flatter, clast lithologies include more quartz and mudstone grains, and there is decadal-scale net erosion. Wave modeling suggests the Mattole headwall region is subject to sustained sheltering from waves due to canyon bathymetry, littoral sediment convergence above the canyon head for much of a typical year, and occasional bed entrainment of sediment in the canyon’s uppermost gullies by large waves. Larger winter waves from the northwest likely result in net southerly drift north of the canyon head, with a high likelihood of preferentially transporting fine-grained, more quartz-rich sediment towards the Mattole headwall. Smaller summer swells from the west and south likely results in net northerly transport of metasandstone clast-rich Mattole River-derived sediment towards the canyon head. The imbalance in seasonality in wave conditions, coast shape, and sediment delivery by the Mattole River and other coastal creeks is broadly consistent with the spatial patterns in grain size, mineralogy, slope, and beach width that we observe in the vicinity of the canyon, and the net delivery of sediment to the Mattole Canyon head. An approximate mass balance of sediment flux from coastal streams feeding Mattole River littoral cell suggests that sediment volumes likely accumulate in the canyon headwall region that could supply several density flow events in a typical decade. These findings highlight the importance of the connectivity of the canyon to the nearshore region for the processes and products in canyons and fans. We hypothesize that feedbacks between canyon bathymetry, sediment accumulation, and mass evacuating flows promotes the long-term persistence of canyon systems.